2007
DOI: 10.2522/ptj.20060192
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Examination of a Proposed Treatment-Based Classification System for Patients Receiving Physical Therapy Interventions for Neck Pain

Abstract: Background and PurposeNeck pain frequently is managed by physical therapists. The development of classification methods for matching interventions to subgroups of patients may improve clinical outcomes. The purpose of this study was to describe a proposed classification system for patients with neck pain by examining data for consecutive patients receiving physical therapy interventions.Subjects and MethodsStandardized methods for collecting baseline and intervention data were used for all patients receiving p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
1
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(70 citation statements)
references
References 64 publications
1
63
1
5
Order By: Relevance
“…18,19,40 Despite a lack of evidence, traction appears to be a common intervention provided by physical therapists, particularly for patients with neck pain accompanied by signs of radiculopathy. 8,16,17 Most studies examining the effectiveness of traction, however, have included patients with nonspecific neck pain and generally have not supported the intervention. 3,10,31,49 The few previous studies examining only patients with radiculopathy have produced mixed results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…18,19,40 Despite a lack of evidence, traction appears to be a common intervention provided by physical therapists, particularly for patients with neck pain accompanied by signs of radiculopathy. 8,16,17 Most studies examining the effectiveness of traction, however, have included patients with nonspecific neck pain and generally have not supported the intervention. 3,10,31,49 The few previous studies examining only patients with radiculopathy have produced mixed results.…”
Section: Discussionmentioning
confidence: 99%
“…Cervical traction is another frequently recommended, yet inadequately researched, treatment for patients with cervical radiculopathy. 35,36 Despite its common use by physical therapists and other providers, 15,16 clinical trials that have examined cervical traction have not found the intervention to be superior to other strategies. 18,40,48 Several factors might have influenced the effectiveness of cervical traction in prior clinical trials.…”
Section: T T Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…While preliminary reports suggest that a multimodal treatment program consisting of manual therapy and exercise may result in positive outcomes for patients with CR, [6][7][8][9][10] efforts to successfully add cervical traction to a multimodal treatment program remain elusive. A study by Ragonese 11 concluded that when treating patients with a diagnosis of CR, an approach that combines manual therapy (including cervical traction) and therapeutic exercise appears to be superior to either intervention alone.…”
Section: Introductionmentioning
confidence: 99%
“…The criteria were implemented to permit the evaluation of clinical outcomes. 12,15 that exceed measurement error. 16,17 The study protocol was approved by the Institutional Review Board of Intermountain Healthcare.…”
Section: Methods Participantsmentioning
confidence: 99%